Pharmacokinetics of Cannabidiol in Rat Brain Tissue After Single-Dose Administration of Different Formulations - Zuzana Binova; Frantisek Benes; Marie Zlechovcova; Matej Maly; Petr Kastanek; Monika Cahova; Milena Stranska; Jana Hajslova (Molecules)
Cannabidiol (CBD), a phytocannabinoid commonly isolated from chemotype III Cannabis sativa plants, is known for its therapeutic potential. However, comprehensive information on its bioavailability is still lacking. The key objective of this study was to investigate the impact of specific formulations on CBD delivery to the site of action and, in particular, the brain of experimental animals. As brain tissue is an extremely complex matrix, a highly sensitive method employing liquid chromatography–tandem mass spectrometry (LC-MS/MS) had to be implemented. To make it applicable for multiple analytes, the method was validated for 17 other phytocannabinoids and selected metabolites. Using this method, a pharmacokinetic study was conducted on 200 brain samples collected from rats that had been administered various CBD formulations (carriers) via oral gavage. The peak concentration in brain occurred within 1–2 h; notably, the highest was reached with carriers containing triacylglycerols with the shortest fatty acid chains (caprylic/capric). In addition to the parent compound, 7-hydroxy-cannabidiol and 7-carboxy-cannabidiol were detected, confirming rapid post-administration metabolism. Overall, this research enhances understanding of CBD distribution in the brain and underscores the impact of specific formulations on its bioavailability, offering insights into optimizing CBD-based therapies to be both effective and ‘patient-friendly’.